Witeflies (Hemiptera: Aleyriridae) of economic importance and their natural enemies (Heminoptera: Aphelinidae, Signiphoridae) in Argentina - Viscarret, M.M.=700 1 Botto, E.N.; Polaszek, A.
(Es, En)
Ilus., 24 ref.
Keywords: HEMIPTERA; ALEYRORIDAE; HUESPEDES; RELACIONES PLANTA ANIMAL; ENEMIGOS NATURALES; CHILE; REVISTA CHILENA DE ENTOMOLOGIA